Nitrite reductase electrode, preparation method thereof and electrochemical system

By introducing transition metal phosphide and electrostatic self-assembly technology on the carbon-based electrode surface of the nitrite reductase electrode, combined with the alternating electric field deposition method, an efficient nitrite reductase electrode was prepared, solving the problems of inefficiency and poor selectivity in the prior art, and achieving high sensitivity and high selectivity detection effects.

CN119846037AActive Publication Date: 2025-04-18TSINGHUA UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411998244.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing nitrite reductase electrodes have problems of low efficiency and poor selectivity during the nitrite detection and conversion process, and the enzyme load is insufficient and it is difficult to achieve repetition of multiple cycles.

Method used

By introducing transition metal phosphides on the surface of the carbon-based electrode, an alternating layer structure is formed, and combined with electrostatic self-assembly technology and alternating electric field deposition method, a nitrite reductase electrode is prepared to improve the enzyme loading rate and catalytic activity.

Benefits of technology

The detection of nitrite is achieved with high sensitivity and high selectivity, and the reduction of nitrite is promoted through electrochemical methods, which improves the reusability and catalytic efficiency of the enzyme electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005226049350000011
    Figure HDA0005226049350000011
  • Figure HDA0005226049350000012
    Figure HDA0005226049350000012
  • Figure HDA0005226049350000021
    Figure HDA0005226049350000021
Patent Text Reader

Abstract

The invention relates to a nitrite reductase electrode, a preparation method thereof and an electrochemical system. The nitrite reductase electrode comprises a substrate layer and an alternating layer of n electron transport layers and n enzyme active layers, the n electron transport layers and the n enzyme active layers are located on the substrate layer, n ranges from 2 to 30, the substrate layer comprises a carbon-based electrode loaded with transition metal phosphide, and the enzyme active layers comprise nitrite reductase. The nitrite reductase electrode disclosed by the invention is low in detection limit value, high in sensitivity, high in enzyme loading rate and high in electro-catalysis efficiency, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a nitrite reductase electrode and a preparation method thereof, and an electrochemical system. Background Art

[0002] Nitrite is a common pollutant in industrial wastewater and contaminated groundwater. It is also a potentially harmful chemical. Excessive intake can cause methemoglobinemia, leading to tissue hypoxia, which can be fatal in severe cases. Long-term exposure may also increase the risk of certain types of cancer. Nitrite reductase (NiRs) is a key enzyme that converts nitrite (NO2 - ) is converted into nitric oxide (NO) or ammonia (NH3), playing a vital role in the nitrogen cycle and nitrogen pollution control. Enzyme-catalyzed reactions are ubiquitous in nature, but are limited by the slow process of energy input consumption and electron transfer in organisms, as well as the high cost of free enzyme extraction and easy inactivation. The enzyme-electrocatalytic technology with immobilized enzymes as the core combines the specificity of enzyme catalysis with the characteristics of directional electron input of electrocatalysis, ensuring that the enzyme-electrocatalytic system has the advantages of sensitivity, efficiency, economy and stability.

[0003] At present, the main enzyme immobilization technologies include physical and chemical processes such as adsorption, embedding, and covalent cross-linking. The adsorption method is simple to operate and has mild immobilization conditions, but its stability is poor; the embedding method is suitable for the immobilization of a variety of enzymes, but there may be problems with enzyme leakage and diffusion restriction of macromolecular substrates; although the covalent cross-linking method has a better immobilization effect, the reaction conditions are harsh, which often causes irreversible effects on enzyme activity, and the overall conductivity is poor. The use of an external electric field to induce the (de)protonation of the electrically neutral functional groups of protein molecules makes it easier to form surface electrostatic potential wells and deposit on the electrode surface. The electrodeposition technology directly loads the enzyme on the conductive substrate through electrostatic attraction, which can greatly improve the sensitivity and conductivity of the enzyme electrode, and retain the structure and catalytic stability of the enzyme, but this method is very likely to cause enzyme loss and lacks repeatability in multiple cycles.

[0004] Therefore, there is a need for an improved nitrite reductase electrode and a preparation method and an electrochemical system thereof. Summary of the invention

[0005] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0006] The present application provides a nitrite reductase electrode, comprising a substrate layer and alternating layers of n electron transport layers and n enzyme active layers located on the substrate layer, wherein n is in the range of 2-30 (n is a positive integer), wherein the substrate layer comprises a carbon-based electrode loaded with a transition metal phosphide, and the enzyme active layer comprises nitrite reductase.

[0007] In one embodiment, n is in the range of 10-20.

[0008] In one embodiment, the loading rate of nitrite reductase on the carbon-based electrode is 10% to 70%.

[0009] In one embodiment, the loading amount of transition metal phosphide on the carbon-based electrode is 0.2-1.5 mg / cm 2 , such as 0.3-0.5mg / cm 2 .

[0010] In one embodiment, the electron transport layer includes reduced graphene oxide having a zeta potential in the range of -2 to -10 mV.

[0011] In one embodiment, the nitrite reductase is a cytochrome c nitrite reductase (CcNIR or NrfA) having a zeta potential in the range of 2-10 mV.

[0012] In the present application, the loaded transition metal phosphide can be used to adsorb protons or dissociate water molecules to generate protons; the reduced graphene oxide forming the electron transport layer can be used to enhance the electron transfer from the electrode to the enzyme and improve the compatibility between the enzyme and the metal layer; the nitrite reductase forming the enzyme active layer can serve as a catalytic site and play a major catalytic role.

[0013] In one embodiment, the nitrite reductase electrode may further include a substrate layer and alternating layers of n electron transport layers and n-1 enzyme active layers located on the substrate layer. That is, the outermost layer is reduced graphene oxide, and the reduced graphene oxide layer can be used to wrap the enzyme active layer from the outside to form a stable composite structure and protect the enzyme.

[0014] In the present application, the cytochrome c type nitrite reductase may be formed by cytochrome c type nitrite reductase extracted from commercially available Shewanella, and its zeta potential is about 2 to 10 mV.

[0015] In one embodiment, the transition metal phosphide is selected from the group consisting of copper phosphide, cobalt phosphide, nickel phosphide and iron phosphide.

[0016] In one embodiment, the carbon-based electrode is selected from one of a glassy carbon electrode, a graphite electrode, carbon paper, carbon cloth, and carbon felt.

[0017] In one embodiment, the carbon felt includes one of polyacrylonitrile-based carbon felt, viscose-based carbon felt, asphalt-based carbon felt, and wood fiber-based carbon felt.

[0018] On the other hand, the present application provides a method for preparing the above-mentioned nitrite reductase electrode, comprising applying an alternating electric field for 2-30 cycles to sequentially electrodeposit the reduced graphene oxide and nitrite reductase in the mixed solution onto a carbon-based electrode loaded with a transition metal phosphide to form the nitrite reductase electrode on which nitrite reductase is fixed.

[0019] In one embodiment, the mixed solution is formed by stirring and mixing 200-800 μl of nitrite reductase solution with 10 ml of phosphate buffer solution, and then adding 5 ml of reduced graphene oxide dispersion and stirring and mixing;

[0020] In one embodiment, the nitrite reductase solution is prepared by dissolving 0.1-1.0 mg / mL of nitrite reductase enzyme in a buffer having a pH range of 6.5-7 (eg, HEPES buffer).

[0021] In one embodiment, the nitrite reductase solution and the phosphate buffer solution are mixed with stirring at 2-8°C.

[0022] In one embodiment, the reduced graphene oxide dispersion is prepared by mixing graphene oxide powder in 0.1-1.0 mg / mL ascorbic acid and ammonia water, and hydrothermally treating the mixture at 90-120° C. for 1-5 h to obtain a reduced graphene oxide dispersion having a concentration of 0.5-1.0 mg / mL, and adjusting the pH of the reduced graphene oxide dispersion to 3-9, preferably 3-6.

[0023] In one embodiment, the transition metal phosphide can be synthesized by first synthesizing a metal hydroxide precursor by a hydrothermal method, and then pyrolyzing and gas-solid phase phosphating to synthesize the transition metal phosphide. The preparation of the carbon-based electrode loaded with the transition metal phosphide can include placing a pre-treated (such as acid-washed) carbon-based electrode such as carbon felt in a transition metal nitrate (such as cobalt nitrate) and urea solution for hydrothermal reaction to obtain a carbon-based electrode loaded with a metal hydroxide (such as cobalt hydroxide) precursor, and then performing phosphating treatment with sodium hypophosphite as a phosphorus source to obtain a carbon-based electrode loaded with the metal phosphide.

[0024] In one embodiment, the total volume of the mixed solution is 20-40 mL.

[0025] In one embodiment, the total stirring time may be 20 to 60 minutes.

[0026] In one embodiment, applying an alternating electric field includes using the mixed solution as an electrolyte, a carbon-based electrode loaded with a transition metal phosphide as a working electrode, a platinum sheet as a counter electrode, and silver-silver chloride as a reference electrode, and applying positive and negative potentials alternately for a total of 2 to 30 cycles to sequentially deposit reduced graphene oxide and nitrite reductase on the working electrode to form the initial electrode, and freeze-drying the initial electrode to obtain the nitrite reductase electrode.

[0027] In one embodiment, the conditions of the alternating electric field include a positive potential of +0.7 to +1.0 V, a single duration of 10s to 20s; a negative potential of -0.5 to -0.8 V, a single duration of 10s to 15s.

[0028] In one embodiment, the last applied alternating electric field is a positive potential. In the present application, the last application of a positive potential forms a reduced graphene oxide layer as the outermost electron transport layer.

[0029] In one embodiment, after forming the initial electrode, the initial electrode may be immersed in pure water for 10 to 30 minutes to remove residual phosphate ions in the electrode gaps and on the surface; and then the initial electrode is freeze-dried to obtain the nitrite reductase electrode.

[0030] In yet another aspect, the present application provides an electrochemical system for detecting nitrite content in water, comprising the above-mentioned nitrite reductase electrode as a cathode.

[0031] In yet another aspect, the present application provides a biosensor comprising the above-mentioned nitrite reductase electrode.

[0032] The present application combines nitrite reductase with reduced graphene oxide, a two-dimensional flexible nanomaterial, and utilizes the principle of electrostatic self-assembly to form a nearly neutral nanoassembly of nitrite reductase and reduced graphene oxide with opposite charge properties in a solution; then, under the action of an alternating electric field, the enzyme migrates to the metal phosphide surface with a stronger local field strength through surface dipole and electrophoretic force, thereby forming a stable enzyme electrode; through periodic reversal of the electric field, reduced graphene oxide and nitrite reductase form a stable conformation on the surface of the carbon-based electrode, and effectively controls the coverage of the assembly on the electrode surface, thereby maximizing the electron donation capacity of the electrode and the catalytic activity of the enzyme.

[0033] The nitrite reductase electrode of the present application overcomes the problems of low efficiency and poor selectivity in the process of nitrite detection and conversion of enzyme electrodes with enzymes as active sites, thereby obtaining a detection electrode with high enzyme loading rate, sensitive detection, strong catalytic activity and reusability, which provides an important supplement to the detection and conversion technology of nitrite nitrogen pollution in surface water and groundwater.

[0034] The existing unmodified carbon-based conductive substrates are difficult to synthesize enzyme electrodes by alternating electric field deposition due to their smooth surface and uniform electric field distribution, and the enzyme loading is less than 5%. In contrast, the present application introduces metal phosphides on the surface of the conductive carbon-based electrode to enhance its local micro-electric field, thereby inducing the loading of reduced graphene oxide and nitrite reductase assembly on the electrode surface.

[0035] The present application is simple to operate and highly repeatable, and has obvious advantages in synthesizing enzyme electrodes and controlling the loading amount and catalytic activity of nitrite reductase.

[0036] The nitrite reductase electrode of the present application can not only achieve high-sensitivity and high-selectivity detection of nitrite, but also promote the reduction of nitrite by electrochemical methods, providing a new idea for nitrogen cycle and nitrogen pollution remediation.

[0037] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0039] Figure 1 Cyclic voltammetry curves of the nitrite reductase electrode provided in Example 1 of the present application at different nitrite concentrations;

[0040] Figure 2 Cyclic voltammetry curves of the cobalt phosphide / carbon felt electrode without nitrite reductase loading provided in Comparative Example 1 of the present application at different nitrite concentrations;

[0041] Figure 3 The catalytic conversion effect of the nitrite reductase electrode provided in the present application on nitrite of different initial concentrations; and

[0042] Figure 4 The effect of catalyzing nitrite conversion of the nitrite reductase electrode provided in the present application is compared with that of different comparative electrodes. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0044] Unless otherwise specified, the materials used in the following examples and comparative examples are commercially available.

[0045] Example 1

[0046] The method for preparing a nitrite reductase electrode may include the following steps:

[0047] Cells were broken and extracted from Shewanella (commercially available, which can be sourced from the China General Microbiological Culture Collection Center (CGMCC), with a culture collection number of CGMCC 19242), followed by protein purification to obtain a cytochrome c type nitrite reductase with a molecular weight of 45-55 kDa, which was dissolved in a HEPES buffer and stored. The concentration of the nitrite reductase was measured by a BCA protein quantification method to be 0.9 mg / mL;

[0048] 50 mg of graphene oxide powder was mixed in a mixed solution of ascorbic acid and ammonia water at a concentration of 0.1 mg / mL, and hydrothermally treated at 100° C. for 2 h to obtain a reduced graphene oxide dispersion with a concentration of 0.5 mg / mL, and the pH of the reduced graphene oxide dispersion was adjusted to 4;

[0049] 2.0*2.5cm 2 The commercially available polyacrylonitrile carbon felt was pretreated with 68% nitric acid to remove surface impurities. The pretreated carbon felt was first placed in a 100 mg / L cobalt nitrate and 50 mg / L urea solution for hydrothermal reaction at 110 °C for 5 h to obtain a carbon felt loaded with a cobalt hydroxide precursor. Subsequently, sodium hypophosphite was used as a phosphorus source and phosphating treatment was performed at 300 °C for 2 h to obtain a carbon felt loaded with cobalt phosphide. The cobalt phosphide loading was 0.4 mg / cm 2 .

[0050] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of a phosphate buffer solution, and the mixture was stirred at 4°C, and then 5 milliliters of a reduced graphene oxide dispersion having a pH of 4 was added, and the mixture was stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0051] The mixed solution was used as an electrolyte, a carbon felt electrode loaded with cobalt phosphide was used as a working electrode, a platinum sheet was used as a counter electrode, and silver-silver chloride was used as a reference electrode. An alternating electric field was applied on an electrochemical workstation for deposition. Under a positive current, the positive potential used was +0.7 V, and the single duration was 15 s. The negative potential used was -0.7 V, and the single duration was 10 s. The positive and negative potentials were alternated for a total of 20 cycles to obtain an electrode for immobilized nitrite reductase.

[0052] The initial electrode was taken out and immersed in pure water for 20 minutes to remove the phosphate buffer remaining in the electrode pores and on the surface. The electrode was freeze-dried and stored at 4°C. The protein concentration change in the mixed solution before and after deposition was tested, and the actual loading rate (enzyme loading rate) on the electrode was 68%.

[0053] The nitrite reductase-reduced graphene oxide-cobalt phosphide electrode synthesized in Example 1 was applied to the electrochemical detection of low-concentration nitrite. Cyclic voltammetry experiments were performed in the voltage range of +0.2V to -1.0V at a scan rate of 50mV / s. The electrolyte was 0.01M PBS and different concentrations of nitrite. The results showed that Figure 1 middle.

[0054] from Figure 1 It can be seen that the nitrite reductase electrode of this embodiment has a significant reduction peak at a potential of -0.67 V, a significant current increase occurs when the nitrite concentration is 140 μM, and the peak current density increases with the increase of nitrite concentration.

[0055] Comparative Example 1

[0056] The method for preparing a nitrite reductase electrode may include the following steps:

[0057] Cells were broken and extracted from commercially available Shewanella strains, followed by protein purification to obtain cytochrome c-type nitrite reductase with a molecular weight of 45-55 kDa. The concentration of nitrite reductase was measured by BCA protein quantification method to be 0.9 mg / mL.

[0058] 50 mg of commercially available graphene oxide powder was mixed in a 0.1 mg / mL mixed solution of ascorbic acid and ammonia water, and hydrothermally treated at 100° C. for 2 h to obtain a reduced graphene oxide dispersion with a concentration of 0.5 mg / mL, and the pH of the reduced graphene oxide dispersion was adjusted to 4;

[0059] 2.0*2.5cm 2 The commercially available polyacrylonitrile carbon felt was pretreated by 68% nitric acid pickling to remove surface impurities, thereby obtaining pretreated carbon felt.

[0060] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of a phosphate buffer solution, and the mixture was stirred at 4°C, and then 5 milliliters of a reduced graphene oxide dispersion was added, and the mixture was stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0061] Using the mixed solution as the electrolyte, the polyacrylonitrile carbon felt electrode as the working electrode, the platinum sheet as the counter electrode, and the silver-silver chloride as the reference electrode, an alternating electric field was applied on the electrochemical workstation for deposition. Under positive current, the positive potential used was +0.7V, the single duration was 15s, the negative potential used was -0.7V, the single duration was 10s, and the positive and negative potentials were alternated for a total of 20 cycles to obtain the initial electrode of immobilized nitrite reductase.

[0062] The initial electrode was taken out and soaked in pure water for 20 minutes to remove the phosphate buffer remaining in the electrode pores and on the surface. The electrode was freeze-dried and stored at 4°C. By testing the change in protein concentration in the mixed solution before and after deposition, the actual loading rate (enzyme loading rate) on the electrode was found to be only 3.4%.

[0063] The nitrite reductase-reduced graphene oxide-carbon felt electrode synthesized in Comparative Example 1 was applied to the electrochemical detection of low-concentration nitrite. Cyclic voltammetry experiments were performed in the voltage range of +0.2V to -1.0V at a scan rate of 50mV / s. The electrolyte was 0.01M PBS and different concentrations of nitrite. The results showed that Figure 2 middle.

[0064] Depend on Figure 2 It can be seen that when the concentration of nitrite added in this comparative example is 420 μM, there is no obvious reduction peak and increase in peak current on the cyclic voltammetry curve, indicating that its sensitivity to low concentration nitrite is low.

[0065] Example 2

[0066] The method for preparing a nitrite reductase electrode may include the following steps:

[0067] Cells were broken and extracted from commercially available Shewanella strains, followed by protein purification to obtain cytochrome c-type nitrite reductase with a molecular weight of 45-55 kDa. The concentration of nitrite reductase was measured by BCA protein quantification method to be 0.9 mg / mL.

[0068] 50 mg of graphene oxide powder was mixed in a mixed solution of ascorbic acid and ammonia water at a concentration of 0.1 mg / mL, and hydrothermally treated at 100° C. for 2 h to obtain a reduced graphene oxide dispersion with a concentration of 0.5 mg / mL, and the pH of the reduced graphene oxide dispersion was adjusted to 3;

[0069] 2.0*2.5cm 2The commercially available polyacrylonitrile carbon felt was pretreated with 68% nitric acid to remove surface impurities. The pretreated carbon felt was first placed in a 100 mg / L cobalt nitrate and 50 mg / L urea solution for hydrothermal reaction at 110 °C for 5 h to obtain a carbon felt loaded with a cobalt hydroxide precursor. Subsequently, sodium hypophosphite was used as a phosphorus source and phosphating treatment was performed at 300 °C for 2 h to obtain a carbon felt loaded with cobalt phosphide. The cobalt phosphide loading was 0.4 mg / cm 2 .

[0070] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of an acidic phosphate buffer solution, and stirred at 4°C, and then 5 milliliters of an acidic reduced graphene oxide dispersion adjusted to pH 3 was added, and stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0071] The mixed solution was used as the electrolyte, the carbon felt electrode loaded with cobalt phosphide was used as the working electrode, the platinum sheet was used as the counter electrode, and the silver-silver chloride was used as the reference electrode. An alternating electric field was applied on the electrochemical workstation for deposition. Under positive current, the positive potential used was +0.7V, and the single duration was 15s. The negative potential used was -0.7V, and the single duration was 10s. The positive and negative potentials were alternated for a total of 20 cycles to obtain an electrode for immobilized nitrite reductase.

[0072] The initial electrode was taken out and immersed in pure water for 20 minutes to remove the phosphate buffer remaining in the electrode pores and on the surface. The electrode was freeze-dried and stored at 4°C. By testing the change in protein concentration in the mixed solution before and after deposition, the actual loading rate (enzyme loading rate) on the electrode was found to be 42%.

[0073] Example 3

[0074] The method for preparing a nitrite reductase electrode may include the following steps:

[0075] Cells were broken and extracted from commercially available Shewanella strains, followed by protein purification to obtain cytochrome c-type nitrite reductase with a molecular weight of 45-55 kDa. The concentration of nitrite reductase was measured by BCA protein quantification method to be 0.9 mg / mL.

[0076] 50 mg of graphene oxide powder was mixed in a mixed solution of ascorbic acid and ammonia water at a concentration of 0.1 mg / mL, and hydrothermally treated at 100° C. for 2 h to obtain a reduced graphene oxide dispersion with a concentration of 0.5 mg / mL, and the pH of the reduced graphene oxide dispersion was adjusted to 4;

[0077] 2.0*2.5cm 2The commercially available polyacrylonitrile carbon felt was pretreated with 68% nitric acid to remove surface impurities. The pretreated carbon felt was first placed in a 100 mg / L ferric nitrate and 50 mg / L urea solution for hydrothermal reaction at 110 °C for 5 h to obtain a carbon felt loaded with an iron hydroxide precursor. Then, sodium hypophosphite was used as a phosphorus source and phosphating treatment was performed at 300 °C for 2 h to obtain a carbon felt loaded with iron phosphide. The iron phosphide loading was 0.3 mg / cm 2 .

[0078] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of an acidic phosphate buffer solution, and the mixture was stirred at 4°C. Then, 5 milliliters of an acidic reduced graphene oxide dispersion solution having a pH adjusted to 4 was added, and the mixture was stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0079] The mixed solution was used as the electrolyte, the carbon felt electrode loaded with iron phosphide was used as the working electrode, the platinum sheet was used as the counter electrode, and the silver-silver chloride was used as the reference electrode. An alternating electric field was applied on the electrochemical workstation for deposition. Under positive current, the positive potential used was +0.7V, and the single duration was 15s. The negative potential used was -0.7V, and the single duration was 10s. The positive and negative potentials were alternated for a total of 20 cycles to obtain an electrode for immobilized nitrite reductase.

[0080] The initial electrode was taken out and immersed in pure water for 20 minutes to remove the phosphate buffer remaining in the electrode pores and on the surface. The electrode was freeze-dried and stored at 4°C. By testing the change in protein concentration in the mixed solution before and after deposition, the actual loading rate (enzyme loading rate) on the electrode was found to be 53%.

[0081] Performance Testing

[0082] Test Example 1

[0083] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of a phosphate buffer solution, and the mixture was stirred at 4°C, and then 5 milliliters of a reduced graphene oxide dispersion was added, and the mixture was stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0084] The mixed solution was used as the electrolyte, and the 2The carbon felt electrode loaded with cobalt phosphide was used as the working electrode, the platinum sheet was used as the counter electrode, and the silver-silver chloride was used as the reference electrode. An alternating electric field was applied on the electrochemical workstation for deposition. Under positive current, the positive potential used was +0.7V, and the single duration was 15s. The negative potential used was -0.7V, and the single duration was 10s. The positive and negative potentials were alternated for a total of 20 cycles to obtain an electrode for immobilized nitrite reductase.

[0085] A nitrite reductase electrode was used as the cathode, a platinum electrode was used as the anode, 35 mL of nitrite with initial concentrations of 1, 2, and 3 mM was added to the electrolyte, and the concentration was 1 mA cm -2 The enzyme electrocatalytic reduction experiment was carried out under low current density conditions. Figure 3 middle.

[0086] Depend on Figure 3 The results show that as the catalytic time increases from 15 minutes to 180 minutes, the treatment efficiency continues to increase, and the conversion rate of nitrate in the solution also increases accordingly. The final nitrite conversion rates reach 96.5%, 94.0% and 84.6%, respectively. According to the change in nitrite concentration, the reaction rate and efficiency at this time are mainly limited by the electron supply. It can be foreseen that when the external circuit provides sufficient electrons, increasing the current density will further improve the catalytic conversion effect of nitrite.

[0087] Test Example 2

[0088] 400 microliters of a nitrite reductase solution having a protein concentration of 0.9 mg / mL was added to 10 milliliters of a phosphate buffer solution, and the mixture was stirred at 4°C, and then 5 milliliters of a reduced graphene oxide dispersion was added, and the mixture was stirred at room temperature for 30 minutes to obtain a nitrite reductase-reduced graphene oxide combined mixed solution;

[0089] The mixed solution was used as the electrolyte, and the 2 The carbon felt electrode loaded with cobalt phosphide was used as the working electrode, the platinum sheet was used as the counter electrode, and the silver-silver chloride was used as the reference electrode. An alternating electric field was applied on the electrochemical workstation for deposition. Under positive current, the positive potential used was +0.7V, and the single duration was 15s. The negative potential used was -0.7V, and the single duration was 10s. The positive and negative potentials were alternated for a total of 20 cycles to obtain an electrode for immobilized nitrite reductase.

[0090] A nitrite reductase electrode was used as the cathode, a platinum electrode was used as the anode, 35 mL of nitrite with an initial concentration of 1 mM was added to the electrolyte, and the electrolyte was stirred at 1 mA cm -2 The enzyme electrocatalytic reduction experiment was carried out under low current density conditions. Figure 4It can be seen from the results that as the catalytic time increases from 15 minutes to 180 minutes, the treatment efficiency continues to improve, and the conversion rate of nitrite in the solution also increases accordingly. The final nitrite conversion rate reaches 96%, indicating that most of the nitrite substrate in the solution is efficiently converted by the nitrite reductase electrode.

[0091] Test Example 3

[0092] 2.0*2.5cm 2 The commercially available polyacrylonitrile carbon felt was pretreated by 68% nitric acid pickling to remove surface impurities, thereby obtaining pretreated carbon felt.

[0093] The pretreated carbon felt was used as the cathode, the platinum electrode was used as the anode, 35 mL of nitrite with an initial concentration of 1 mM was added to the electrolyte, and the electrolyte was heated at 1 mA cm -2 The enzyme electrocatalytic reduction experiment was carried out under low current density conditions. Figure 4 It can be seen from the results that as the catalytic time increases from 15 minutes to 180 minutes, the treatment efficiency continues to improve, and the conversion rate of nitrite in the solution also increases accordingly. The final nitrite conversion rate reaches 58.5%, indicating that only part of the nitrite in the solution is completely converted, the residual nitrite is large, and the catalytic effect is poor.

[0094] Test Example 4

[0095] 2.0*2.5cm 2 The commercially available polyacrylonitrile carbon felt was pretreated by pickling with 68% nitric acid to remove surface impurities. The pretreated carbon felt was first placed in a 100 mg / L cobalt nitrate and 50 mg / L urea solution and hydrothermally reacted at 110°C for 5 hours to obtain carbon felt loaded with a cobalt hydroxide precursor. Subsequently, sodium hypophosphite was used as a phosphorus source and phosphating treatment was carried out at 300°C for 2 hours to obtain carbon felt loaded with cobalt phosphide.

[0096] Cobalt phosphide-loaded carbon felt was used as the cathode, and a platinum electrode was used as the anode. 35 mL of nitrite with an initial concentration of 1 mM was added to the electrolyte at 1 mA cm -2 The enzyme electrocatalytic reduction experiment was carried out under low current density conditions. Figure 4 It can be seen from the results that as the catalytic time increases from 15 minutes to 180 minutes, the treatment efficiency continues to improve, and the conversion rate of nitrite in the solution also increases accordingly. The final nitrite conversion rate reaches 80.9%, and its catalytic effect is improved compared to carbon felt. However, the catalytic rate slows down significantly in the later stage of the reaction, and there is still nitrite residual in the solution.

[0097] Test Example 5

[0098] Without adding nitrite reductase, 5 ml of the reduced graphene oxide dispersion was added to 10 ml of the phosphate buffer solution and stirred at room temperature for 30 minutes to obtain a reduced graphene oxide solution.

[0099] 2.0*2.5cm 2 The commercially available polyacrylonitrile carbon felt was pretreated by pickling with 68% nitric acid to remove surface impurities. The pretreated carbon felt was first placed in a 100 mg / L cobalt nitrate and 50 mg / L urea solution and hydrothermally reacted at 110°C for 5 hours to obtain carbon felt loaded with a cobalt hydroxide precursor. Subsequently, sodium hypophosphite was used as a phosphorus source and phosphating treatment was carried out at 300°C for 2 hours to obtain carbon felt loaded with cobalt phosphide.

[0100] The above-mentioned reduced graphene oxide mixed solution was used as an electrolyte, a carbon felt electrode loaded with cobalt phosphide was used as a working electrode, a platinum sheet was used as a counter electrode, and silver-silver chloride was used as a reference electrode. An alternating electric field was applied on an electrochemical workstation for deposition. Under a positive current, the positive potential used was +0.7V, and the single duration was 15s. The negative potential used was -0.7V, and the single duration was 10s. The positive and negative potentials were alternated for a total of 20 cycles to obtain a reduced graphene oxide electrode.

[0101] The deposited reduced graphene oxide-cobalt phosphide electrode was taken out and immersed in pure water for 20 minutes to remove the phosphate buffer remaining in the electrode pores and on the surface. The electrode was freeze-dried and stored at 4°C.

[0102] A reduced graphene oxide-cobalt phosphide electrode was used as the cathode, a platinum sheet electrode was used as the anode, 35 mL of nitrite with an initial concentration of 1 mM was added to the electrolyte, and the electrolyte was heated at 1 mA cm -2 The enzyme electrocatalytic reduction experiment was carried out under low current density conditions. Figure 4 It can be seen from the results that as the catalytic time increases from 15 minutes to 180 minutes, the treatment efficiency continues to improve, and the conversion rate of nitrite in the solution also increases accordingly. The final nitrite conversion rate reaches 79.2%. In the later stage of the reaction, the catalytic rate slows down significantly, and there is still residual nitrite in the solution.

[0103] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Those skilled in the art can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A nitrite reductase electrode, characterized in that: The invention comprises a substrate layer and alternating layers of n electron transport layers and n enzyme active layers located on the substrate layer, wherein n is in the range of 2-30, wherein the substrate layer comprises a carbon-based electrode loaded with transition metal phosphide, and the enzyme active layer comprises nitrite reductase.

2. The nitrite reductase electrode according to claim 1, characterized in that The nitrite reductase electrode comprises a substrate layer and alternating layers of n electron transport layers and n-1 enzyme active layers located on the substrate layer.

3. The nitrite reductase electrode according to claim 1, characterized in that: The loading rate of nitrite reductase on the carbon-based electrode is 10% to 70%.

4. The nitrite reductase electrode according to claim 1, characterized in that: The loading amount of transition metal phosphide on the carbon-based electrode is 0.2-1.5 mg / cm 2 .

5. The nitrite reductase electrode according to any one of claims 1 to 4, characterized in that The nitrite reductase is selected from any one of copper-type nitrite reductase, cytochrome cd1-type nitrite reductase, polyheme c nitrite reductase and ferredoxin-dependent nitrite reductase; optionally, the nitrite reductase is a cytochrome c-type nitrite reductase having a zeta potential in the range of 2 to 10 mV, and / or, The electron transport layer includes reduced graphene oxide having a zeta potential in the range of -2 to -10 mV.

6. The nitrite reductase electrode according to any one of claims 1 to 4, characterized in that The transition metal phosphide is selected from the group consisting of copper phosphide, cobalt phosphide, nickel phosphide and iron phosphide; Optionally, the carbon-based electrode is selected from one of a glassy carbon electrode, a graphite electrode, carbon paper, carbon cloth, and carbon felt; Optionally, the carbon felt includes one of polyacrylonitrile-based carbon felt, viscose-based carbon felt, asphalt-based carbon felt, and wood fiber-based carbon felt.

7. A method for preparing a nitrite reductase electrode according to any one of claims 1 to 6, characterized in that: The method comprises applying an alternating electric field for 2-30 cycles to sequentially electrodeposit reduced graphene oxide and nitrite reductase in a mixed solution onto a carbon-based electrode loaded with transition metal phosphide to form the nitrite reductase electrode fixed with nitrite reductase.

8. The method according to claim 7, characterized in that The mixed solution is formed by stirring and mixing 200-800 microliters of nitrite reductase solution and 10 milliliters of phosphate buffer solution, and then adding 5 milliliters of reduced graphene oxide dispersion and stirring and mixing; Optionally, the nitrite reductase solution is prepared by dissolving 0.1-1.0 mg / mL of nitrite reductase in a buffer having a pH range of 6.5-7; Optionally, the reduced graphene oxide dispersion is prepared by mixing graphene oxide powder with 0.1-1.0 mg / mL ascorbic acid and ammonia water, and hydrothermally treating the mixture at 90-120° C. for 1-5 h to obtain a reduced graphene oxide dispersion having a concentration of 0.5-1.0 mg / mL, and adjusting the pH of the reduced graphene oxide dispersion to 3-9; Optionally, the total volume of the mixed solution is 20 to 40 mL.

9. The method according to claim 7, characterized in that Applying an alternating electric field includes using the mixed solution as an electrolyte, a carbon-based electrode loaded with a transition metal phosphide as a working electrode, a platinum sheet as a counter electrode, and silver-silver chloride as a reference electrode, and applying positive and negative potentials alternately for a total of 2 to 30 cycles, so as to sequentially deposit reduced graphene oxide and nitrite reductase on the working electrode to form the initial electrode, and freeze-drying the initial electrode to obtain the nitrite reductase electrode; Optionally, the conditions of the alternating electric field include a positive potential of +0.7 to +1.0 V and a single duration of 10s to 20s; The negative potential is -0.5 to -0.8 V, and the single duration is 10s to 15s; Optionally, the last applied alternating electric field is a positive potential.

10. An electrochemical system for detecting nitrite content in water, characterized in that: The electrochemical system comprises a nitrite reductase electrode according to any one of claims 1 to 6 as a cathode.

Citation Information

Patent Citations

  • Acetylcholine esterase electrode adopting foam nickel as carrier, and applications thereof

    CN103257168A

  • Preparation method for carbon cloth electrode based on cobalt phosphide / hemoglobin modification

    CN105403606A

  • Nitrogen-doped porous vertical graphene nanowall array and preparation method and application thereof

    CN107235472A

  • Embedded and seeped foamed nickel cholinesterase electrode and application thereof

    CN107764879A

  • Porous nitrogen-doped graphene composite cobalt phosphide nanosheet and preparation method and application thereof

    CN110983360A